KINERJA PEGAWAI BIRO SDM KEPOLISIAN DAERAH DITINJAU DARI KEPEMIMPINAN MELAYANI DENGAN PERILAKU KEWARGAAN ORGANISASI SEBAGAI MODERATOR - Mutiah Aulia, Andi Intan; Fahmie, Arief (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
Servant leadership plays an important role in determining employee performance through an approach focused on employee needs and empowerment. This study aims to determine the relationship between servant leadership and employees’ performance with employee organizational citizenship behaviour as a moderator variable. The subjects of the study were all 86 employees of the Human Resources Division of Regional Police. Data analysis used Jamovi 2.4.11 with simple regression analysis and moderated multiple regression models. The results of the study showed that servant leadership had a significant impact on improving employee performance at the Human Resources Division of Regional Police which the better the servant leadership obtained from superiors, the higher the employee performance. This study also found that organizational citizenship behaviour could act as a moderator in the relationship between servant leadership and employee performance, but had a significant negative relationship when employees with the high levels of organizational citizenship behaviour and received servant leadership, employee performance tended to decrease due to excessive pressure or fatigue due to the extra contributions that employees make. The results of this study are expected to provide more optimal guidance in implementing servant leadership and encouraging organizational citizenship behaviour, so that it can overall improve employees’ performance.